Breast compression parameters among women screened with standard digital mammography and digital breast tomosynthesis in a randomized controlled trial. (March 2020) - Waade, Gunvor Gipling; Holen, Åsne; Sebuødegård, Sofie; Aase, Hildegunn; Pedersen, Kristin; Hanestad, Berit; Hofvind, Solveig
Background: No evidence-based guidelines regarding optimal breast compression in mammography exist, neither for standard digital mammography nor for digital breast tomosynthesis. Purpose: To compare breast compression parameters and mean glandular dose in a randomized controlled trial with digital mammography versus digital breast tomosynthesis. Material and Methods: We used information from 21, 729 women aged 50–69 years, who participated in the To-Be trial, as part of BreastScreen Norway, 2016–2017. Information was obtained from the DICOM header and by assessing the images in an automated software for density estimation (VolparaDensity). Using linear regression, we investigated the effect of screening technique on breast compression parameters; compression force (N), compression pressure (kPa), and compressed breast thickness (mm), and mean glandular dose (mGy), by view (craniocaudal [CC] and mediolateral oblique [MLO]). We adjusted for age, breast volume and fibroglandular volume. Results: A total of 11, 056 (50.9%) women were screened with digital mammography and 10, 673 (49.1%) with digital breast tomosynthesis. Adjusted regression analysis showed that women undergoing digital mammography received higher compression forces than women undergoing digital breast tomosynthesis (CC: –4.7 N; MLO: –1.1 N, P < 0.001 for both), higher compression pressure (CC: –1.0 k Pa; MLO: –0.1 kPa, P < 0.001 for both), and higher values of compressed breast thickness in the MLO view (–0.3 mm, P = 0.02). The women undergoing digital mammography received a lower mean glandular dose than women undergoing digital breast tomosynthesis ([+]0.06 mGy, P < 0.001). Conclusion: Women undergoing digital breast tomosynthesis received lower compression force, compression pressure, and compressed breast thickness in MLO view, compared to women undergoing digital mammography. Further studies should investigate the impact of breast compression on image quality, screening outcome, and radiation dose for digital mammography and digital breast tomosynthesis in order to establish evidence-based guidelines for breast compression.